(untitled) - Sudarsanam, P. S. (Harlow, England, 2003)
Creating Value from Mergers and Acquisitions gives an integrated and international perspective. This new book builds on and extends the author's highly successful title The Essence of Mergers and Acquisitions. This is the first book to provide a comparative analysis of the M & A scene in Europe and the US, the two most active markets in the world. The book develops an international and multidisciplinary perspective of M & A, and considers M & A as a process and not a mere transaction. The author draws upon economics, finance, strategy, law and organisational theories to formulate a five-stage model and emphasises the need to understand the inter-connected nature of these stages. The book's central focus is on the challenges to using M & A as an instrument to create shareholder value, how M & A risks can be mitigated and how odds of success in acquisitions can be increased. Creating Value from Mergers and Acquisitions is suitable for those studying advanced undergraduate and MBA courses in industrial organisation, finance, business strategy, and corporate governance, as well as those preparing for exams set by professional bodies.
Keywords: Consolidation and merger of corporations.,Corporations,Sự thống nhất và liên kết của các tập đoàn; Valuation